(untitled) (Research, Society and Development, 2023)
The discipline of nutritional assessment, fundamental for the development of nutritionists, is composed of theoretical and practical activities that dedicated dedication and exercise of the contents. However, after returning to face-to-face activities, students found it difficult to adapt and develop learning. This study aims to report the experience of academic monitoring in the return to face-to-face classes, in a hybrid format. This research is of the qualitative and quantitative experience report type, with data collection carried out through a comparison between the averages of the estimates, before and after the beginning of the program and an online dialogue with 7 objective questions, which were incorporated by the students about classification with monitoring. The results showed a 25% increase in the average of the estimates, and 100% satisfaction with the monitor’s activities and ways of working, both face-to-face and remote. With this, the importance of monitoring is reintegrated into practical disciplines in the area of ​​health.